Comparison of treatment routine using aflibercept: Strict vs. relaxed retreatment regimen (TOLERANT study)—A non-inferiority, randomized controlled trial - Jaggi, Damian; Berger, Lieselotte E.; Zweifel, Sandrine; Becker, Matthias D.; Michels, Stephan; Stalder, Odile; Lincke, Joel-Benjamin; Habra, Oussama; Wolf, Sebastian; Zinkernagel, Martin Sebastian (Acta ophthalmologica, 2025)
Purpose This trial evaluated the noninferiority of a relaxed compared to a strict treat-and-extend treatment strategy in patients with neovascular Age-related macular degeneration (AMD). Methods Multicenter, randomized, controlled, phase IV, non-inferiority clinical trial. Patients with treatment-naïve nAMD were randomized 1:1 to a relaxed or strict treat-and-extend treatment regimen. Aflibercept 2 mg/0.05 mL was used. In the relaxed regimen, up to 100 μm subfoveal subretinal fluid was tolerated, vs. no tolerance of any fluid in the strict regimen. The primary outcome was the change in best corrected visual acuity (BCVA; ETDRS letters) from baseline to the end of the study at week 104 and its difference between the two treatment arms, with a 5-letter non-inferiority margin. Results We randomized 150 patients. The full analysis showed non-inferiority of the relaxed treatment, with a mean difference of −0.12 letters (95%-CI: −3.45 to infinity, H0; mean. diff. ≤ 5 letters: p = 0.008), and a visual acuity gain of 7.3 (4.82; 9.78) vs. 7.01 (3.67; 10.36) letters in the strict vs. relaxed regimen, respectively. Many patients deviated from the protocol due to Covid-19. Per-protocol analysis showed a mean difference of −1.78 letters (95%-CI: −6.61 to infinity, H0; mean. diff. ≤ 5 letters: p = 0.136). Fewer injections were needed in the relaxed regimen, with a mean difference of −2.34 (95%-CI: −4.11 to −0.56, p = 0.01). Conclusion Tolerating up to 100 μm subfoveal subretinal fluid achieves good visual outcomes in our 24-month follow-up period, in patients treated with aflibercept for nAMD, with significantly fewer injections needed.
Online verfügbar: 06. Mai 2025
Gesehen am 24.10.2025